Children in the Online World Risk, Regulation, Rights - Staksrud, Elisabeth (Taylor & Francis, 2013)
What is online risk? How can we best protect children from it? Who should be responsible for this protection? Is all protection good? Can Internet users trust the industry? These and other fundamental questions are discussed in this book. Beginning with the premise that the political and democratic processes in a society are affected by the way in which that society defines and perceives risks, Children in the Online World offers insights into the contemporary regulation of online risk for children (including teens), examining the questions of whether such regulation is legitimate and whether it does in fact result in the sacrifice of certain fundamental human rights. The book draws on representative studies with European children concerning their actual online risk experiences as well as an extensive review of regulatory rationales in the European Union, to contend that the institutions of the western European welfare states charged with protecting children have changed fundamentally, at the cost of the level of security that they provide. In consequence, children at once have more rights with regard to their personal decision making as digital consumers, yet fewer democratic rights to participation and protection as 'digital citizens'. A theoretically informed, yet empirically grounded study of the relationship between core democratic values and the duty to protect young people in the media-sphere, Children in the Online World will appeal to scholars and students across the social sciences with interests in new technologies, risk and the sociology of childhood and youth. Book: The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.